Nephrogenic adenoma; A rare entity in chronic irritation or infection of the bladder - (:unkn) unknown (My University, 1996)
A 69 year-old man, with accidental finding of bilateral kidney stones, and two papillary lesions in the bladder is described. His recurrent urinary tract infections were treated according to the suitable antibiotics. His renal functions were impaired moderately, and his cystoendoscopy revealed two papillary lesions on the posterior wall of the bladder. The histopathological examination of the resected tissue revealed nephrogenic adenoma, and the patient would be followed-up with check cystoscopies three monthly periods for the first year. Nephrogenic adenoma is a rare entity, mainly in the male population, with chronic irritation or infection.
Keywords: Bladder; Neoplasm; Nephrogenic adenoma